2011
DOI: 10.15253/2175-6783.20110003000015
|View full text |Cite
|
Sign up to set email alerts
|

Uso do partograma em maternidades escola de Alagoas

Abstract: O objetivo deste estudo foi determinar a frequência de uso do partograma em maternidades escola de Alagoas, Brasil. Foi um estudo descritivo de corte transversal. A amostra constou de 171 prontuários de puérperas assistidas durante o trabalho de parto. Foram coletados dados relativos ao uso do partograma e de seus itens: dilatação cervical, altura da apresentação, variedade de posição, batimentos cardíacos fetais, dinâmica uterina, condições da bolsa, uso de ocitocina, uso de medicamentos/fluidos/anestesia, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In Alagoas State, the most common items of the partogram were the condition of the pouch (61%), identification of the pregnant woman (72%) and real time (93.06%). 9 The present study shows that the variables with the highest fill index were cervical dilatation, pocket conditions, and the examiner's signature.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…In Alagoas State, the most common items of the partogram were the condition of the pouch (61%), identification of the pregnant woman (72%) and real time (93.06%). 9 The present study shows that the variables with the highest fill index were cervical dilatation, pocket conditions, and the examiner's signature.…”
Section: Discussionmentioning
confidence: 51%
“…The sample size was calculated based on a study carried out in maternity reference schools where 42% of the frequency of use of the partogram was observed. 9 Based on this study's data, the sample size was calculated with a proportion in the population of 42%, absolute precision of 7% and a level of significance of 5%, reaching a total of 191 medical records. This calculation was obtained using the estimation of a proportion referring to the population of interest.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, when it is used, the necessary items are not completely filled. 11 In a meta-analysis performed by Lavender, Hart and Smyth, five clinical trials were evaluated, and two studies evaluated the use or not of the partograph involving 1,590 women. It was concluded that there was insufficient evidence to recommend the routine use of it, with no difference between the use of the partograph and the reduction of the cesarean rates.…”
Section: Discussionmentioning
confidence: 99%
“…17 Nevertheless, the indiscriminate use of oxytocin, mainly in the beginning of the labor, leads to the fact that the pain does not follow the dilation, and, with this, the women get exhausted mainly when they perceive that the pain has increased and there is no evolution of this process, often resulting in them choosing a cesarean section. 11 In the “Being Born in Brazil” survey, it was observed that the infusion of oxytocin and amniotomy were techniques widely used to accelerate labor, and were performed in 40% of women at normal risk. 4 In the present study, 65.1% of the professionals reported that this type of procedure is routine in maternity 1, while in maternity 2, 62.8% said they did not perform it.…”
Section: Discussionmentioning
confidence: 99%